Quantifying the economic and demographic impact of transportation infrastructure investments: A simulation study. (April 2016) - Diaz, Rafael; Behr, Joshua G; Ng, ManWo
Investment in transportation infrastructure has been widely utilized as an instrument for inducing economic growth. Such investment usually leads to job creation and an increase in per capita income that attracts population through migration to the region. This increases the utilization of the transport infrastructure over time, resulting in high levels of congestion. The congestion negatively impacts the attractiveness of the region and the gross regional product (GRP). Regions cyclically invest in transport infrastructure that temporally spurs economic activity and migration, and reduces congestion. This research employs a system dynamics simulation approach to capture and mimic the behavior of these complex and cyclical relationships over time. Our approach suggests the modeling of key demographic, transportation infrastructure, travel behavior, and economic activity components to determine the impact of infrastructure investments on regional growth. Given a set of prospective investment scenarios, the model replicates and projects levels of productivity, travel demand, congestion, GRP, and net migration patterns over time. The model also provides insights into the duration of critical cyclical patterns given these prospective infrastructure investments. The simulation model presented in this paper seeks to be utilized as guidance to support decision-making processes that lead to the execution of more exhaustive transportation studies that organize the execution of such investments.